Rethinking Christianity in Pluralistic Cultures: The Challenge of Inter-Faith Dialogue - Narciso, Jerson Benia (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2009)
The author discusses three directions in which Christianity can be rethought: exclusivist, inclusivist and pluralist. While the inclusivist view is better than the exclusivist view, both views do not rethink Christianity in a way that it becomes suitable for a new age, i.e. globalization, in which we all have to deal with people from different faiths. Christianity is seen as superior in both the exclusivist and the inclusivist view. Whereas in the pluralist view Christianity is seen as one among many religions, which make a genuine dialogue possible.